Correlation of the quality attributes of fufu flour and the sensory and instrumental texture profiles of the cooked dough produced from different cassava varieties - Awoyale, W.; Oyedele, H.A.; Adenitan, A.A.; Adesokan, Michael; Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie (Informa UK Limited, 2022)
There is little or no information on the relationship between the quality of fufu flour and the textural attributes of cooked dough. Quality attributes of flour were therefore correlated with the sensory texture profile analysis (STPA) and instrumental texture profile analysis (ITPA) of the dough produced from six varieties of cassava. Results showed that the water absorption capacity (WAC) of flour had a positive correlation (p < .05, r = 0.90) with the STPA moldability of the cooked dough and a significant negative correlation (p < 0 .05, r = −0.94) with its STPA. The correlation between the STPA hardness of cooked dough and the bulk density of flour was positive and significant (p < .01, r = 0.94) but not significant between the ITPA of cooked dough and the quality attributes of flour. The textural attributes of the eba produced from the TMEB419 variety were hardness and moldability, those for TMS13F1020P0001 were stretchability, gumminess, hardness, and adhesiveness, and those for NR14B-218, TMS13F1153P0001, NR1741, and IITA-TMS-IBA30572 were moldability and stretchability. The information provided in this study might help in the breeding of cassava varieties that would be acceptable to end-users in terms of the quality characteristics of flour and the textural attributes of cooked dough.